For the aspiring wildlife biologist - Fuhrmann, Christy, author; White, Cecilia, advisor; Egret, Cookie, committee member (Colorado State University. Libraries, 2025)
For the Aspiring Wildlife Biologist is a narrative-based resource designed to provide practical advice, personal insight, and motivation for undergraduate students pursuing wildlife biology. While classes build necessary knowledge and skills, they often lack the storytelling and personal perspectives that help students understand the realities of the field. To bridge this gap, each chapter features an interview with a wildlife professional – ranging from graduate students and professors to those outside of academia – highlighting pivotal career moments, field experiences, lessons learned, and advice for students. By presenting these perspectives through creative nonfiction, the project emphasizes the power of storytelling to make guidance for aspiring wildlife biology students more memorable and accessible. Ultimately, the book serves as both an introduction to the variety of paths within wildlife biology and a source of encouragement for students navigating their own academic and professional journeys.
Department of Fish, Wildlife, and Conservation Biology/Wildlife Biology concentration.
Keywords: career; college students; conservation; firsthand accounts; guide; honors thesis; interviews; mentorship; narrative; professional development; story; storytelling; undergraduates; wildlife biology